The GULAG press: on the example of the newspaper "Putevka" (Herald of Journalism, 2022)
According to many researchers, the propaganda of the Soviet Union was carried out not only on the entire Soviet population, but also on the prisoners of the GULAG camps and prisons. The newspapers published in the camps were the simple and mostly propaganda tool of Soviet labor. The study of the "Print of the GULAG" is just beginning, and develops as data on the newspapers of the GULAG becomes available.The main purpose of the study is, based on the materials of the newspaper "Putevka", published in Karlag, to find out the main function and role of the newspaper, and the influence of Soviet propaganda on the rehabilitation of prisoners through the press.The scientific originality of the work that the authors for the first time identified and presented a content analysis of the newspaper "Putevka", published in Karlag, as a witness to the history of the GULAG camps and places of correction in Central Kazakhstan.The research methods were based on the basic techniques of the method of qualitative and quantitative analysis of the documents’ content; content analysis of the materials of the newspaper "Putevka" was applied. The genres and themes of the materials are considered and the involvement of prisoners in the work of the newspaper and the content they provide are studied. Also, a historical analysis of the emergence and development of the GULAG press was carried out in order to identify the influence of Soviet propaganda among the prisoners of Karlag.The results of the study showed that the newspaper was an integral part of Soviet propaganda in Karlag. The development of printing in Karlag influences the stimulation and promotion of the constant need for high labor productivity in the GULAG camps.Keywords: Kazakhstan, GULAG, Karlag, Putevka, Soviet Union, newspaper, propaganda, press.